Porous Silica Nanomaterials as Carriers of Biologically Active Natural Polyphenols: Effect of Structure and Surface Modification - Ivalina Trendafilova; Margarita Popova (MDPI AG, 2024)
For centuries, humans have relied on natural products to prevent and treat numerous health issues. However, biologically active compounds from natural sources, such as polyphenols, face considerable challenges, due to their low solubility, rapid metabolism, and instability, which hinder their effectiveness. Advances in the nanotechnologies have provided solutions to overcoming these problems through the use of porous silica materials as polyphenol carriers. These materials possess unique properties, such as a high specific surface area, adjustable particle and pore sizes, and a surface that can be easily and selectively modified, which favor their application in delivery systems of polyphenols. In this review, we summarize and discuss findings on how the pore and particle size, structure, and surface modification of silica materials influence the preparation of efficient delivery systems for biologically active polyphenols from natural origins. The available data demonstrate how parameters such as adsorption capacity, release and antioxidant properties, bioavailability, solubility, stability, etc., of the studied delivery systems could be affected by the structural and chemical characteristics of the porous silica carriers. Results in the literature confirm that by regulating the structure and selecting the appropriate surface modifications, the health benefits of the loaded bioactive molecules can be significantly improved.